Assessing the impact of telephone call intervention on medication adherence in individuals with mental health disorders: A longitudinal study in a tertiary facility in Volta Region - Thelma Alalbila Aku; Ebenezer Wiafe; Samira Mina Alhassan; Peter Yamoah; Eugene Dordoye; Joseph K.N. Nyoagbe; Araba Hutton-Nyameaye; Israel Sefah; Justice Jones; Harrison Awuttey; John K.A. Korbuvi; Varsha Bangalee (Scientific African)
Medication adherence strategies that are successful, suitable and economical are vital to the treatment outcome of persons living with mental illness. Mobile-phone-based intervention is one such strategy and is particularly critical to reducing medication non-adherence, especially in mental health disorders. This study aimed to assess the impact of telephone adherence counselling on medication adherence in persons with mental health disorders. A longitudinal study was conducted on study participants who were randomly assigned to control and intervention groups over three months. Both groups received standard medication adherence counselling for the first month and then baseline adherence levels were determined using the medication adherence rating scale (MARS). The control group received standard medication adherence counselling at the psychiatric clinic whilst the intervention group received additional telephone calls made to each member of the intervention group once a week for a total of 8 times over 2 months. Of the patients who were screened for potential participation, 149 participants passed and 87 participants participated making a response rate of 58.40 %. The t-test conducted on the participants after the first (Month 2) and second (Month 3) on those with Telephone Call Intervention inferred significant statistical differences (p < 0.001). MARS Scores appreciated in the intervention group compared to the control group in Month 2 (1.64) and Month 3 (1.79). A positive impact of Telephone Call Interventions on medication adherence was achieved. This intervention can be a medication adherence strategy to supplement the standard medication adherence counselling which could improve treatment outcomes.